The Compaction of Floodplain Sediments: Timing, Magnitude and Implications - Nadon, G.; Issler, D. (Geoscience Canada, 1997)
Summary Backstripping techniques for basin and stratigraphie analyses assume that the original porosity of the sediments is known within reasonable limits. Erroneous original porosity assumptions lead to serious errors in stratigraphie sections with a significant proportion of fine-grained material. The present algorithms, which assume initial porosities of between 50% and 70% for muds and 40%to 50% for sands, are only applicable to sediments that were never subaerially exposed. Outcrop data from flood plaindeposits show that the differential compaction between sandstones and mud-stones that should be present if those assumptions were correct does not exist. Modern floodplain silts and clays below the liquid limit, i.e., that behave asplastics, have porosities that vary from34% to 39%, and sands have 27-35% porosity. Sections decompacted using the marine shale and sandstone porosity values overestimate the original thickness of flood plain strata by as much as 31%. These errors mean that the estimates of total basin subsidence in regions, such as proximal foreland basins, are seriously over estimated. The subtle inflections in burial history curves, sometimes used to infer either eustatic or tectonic sea-level fluctuations in these basins, are noise rather than signal.